Clarification of some aspects related to genotoxicity assessment. (18th December 2017) - ,; Hardy, Anthony; Benford, Diane; Halldorsson, Thorhallur; Jeger, Michael; Knutsen, Helle Katrine; More, Simon; Naegeli, Hanspeter; Noteborn, Hubert; Ockleford, Colin; Ricci, Antonia; Rychen, Guido; et al.
Abstract: The European Commission requested EFSA to provide advice on the following: (1) the suitability of the unscheduled DNA synthesis (UDS) in vivo assay to follow‐up positive results in in vitro gene mutation tests; (2) the adequacy to demonstrate target tissue exposure in in vivo studies, particularly in the mammalian erythrocyte micronucleus test; (3) the use of data in a weight‐of‐evidence approach to conclude on the genotoxic potential of substances and the consequent setting of health‐based guidance values. The Scientific Committee concluded that the first question should be addressed in both a retrospective and a prospective way: for future assessments, it is recommended no longer performing the UDS test. For re‐assessments, if the outcome of the UDS is negative, the reliability and significance of results should be carefully evaluated in a weight‐of‐evidence approach, before deciding whether more sensitive tests such as transgenic assay or in vivo comet assay would be needed to complete the assessment. Regarding the second question, the Scientific Committee concluded that it should be addressed in lines of evidence of bone marrow exposure: toxicity to the bone marrow in itself provides sufficient evidence to allow concluding on the validity of a negative outcome of a study. All other lines of evidence of target tissue exposure should be assessed within a weight‐of‐evidence approach. Regarding the third question, the Scientific Committee concluded that any available data that may assist in reducing the uncertainty in the assessment of the genotoxic potential of a substance should be taken into consideration. If the overall evaluation leaves no concerns for genotoxicity, health‐based guidance values may be established. However, if concerns for genotoxicity remain, establishing health‐based guidance values is not considered appropriate.